The Efficacy of Phyllanthus niruri Linn in Modulating Inflammatory and Cancer Stem Cell Markers in Colorectal Cancer: A Stratified Systematic Review and Meta-Analysis - Nurul Ahmad Isnaini; Albertus Ari Adrianto; Udadi Sadhana (HM Publisher, 2025)
Background: The progression of colorectal cancer (CRC) is driven by a complex interplay between chronic inflammation and a resilient population of cancer stem cells (CSCs). Phyllanthus niruri Linn (PNL), a medicinal plant with established immunomodulatory effects, presents a promising adjuvant therapeutic strategy. This study aimed to move beyond qualitative summaries to quantitatively assess PNL's efficacy by synthesizing evidence on its modulation of key inflammatory and CSC biomarkers. Methods: Following PRISMA guidelines, a systematic search of PubMed, ScienceDirect, Google Scholar, and Scopus (2015–2025) was conducted. Studies quantifying the effects of PNL on Interleukin-8 (IL-8), Cyclooxygenase-2 (COX-2), or CD133 in CRC models were included. Recognizing the profound biological differences between experimental systems, a stratified meta-analysis was performed. Data were pooled using a random-effects model, stratified by study type (in vitro vs. in vivo) and intervention (monotherapy vs. combination therapy). The Standardized Mean Difference (SMD) was the primary effect measure. Results: Seven studies met the inclusion criteria. In a stratified analysis of in vivo models, PNL monotherapy significantly reduced COX-2 (SMD -2.11; 95% CI [-3.10, -1.12]) and IL-8 (SMD -1.95; 95% CI [-3.01, -0.89]). The effect on the CSC marker CD133 was most pronounced in vitro (SMD -2.98; 95% CI [-4.87, -1.09]), while still significant in in vivo models (SMD -2.15; 95% CI [-3.45, -0.85]). The analysis revealed that the biological context (in vitro vs. in vivo) is a significant determinant of the observed effect size. Conclusion: This stratified meta-analysis provides robust, context-specific evidence of PNL's ability to suppress key inflammatory and CSC markers in CRC. The findings reveal that PNL's potent anti-CSC activity observed in vitro is translated into a significant, though attenuated, effect in vivo, highlighting the critical influence of the tumor microenvironment and pharmacokinetics. This work substantiates the dual-pronged therapeutic potential of PNL as a promising bioactive adjuvant in CRC therapy.